2015
DOI: 10.3892/ijmm.2015.2241
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola rosea suppresses thymus T-lymphocyte apoptosis by downregulating tumor necrosis factor-α-induced protein 8-like-2 in septic rats

Abstract: In recent years, several studies have shown that Rhodiola rosea can enhance cellular immunity and humoral immune function in mice, and thus, it has become a research hotspot. However, its underlying mechanism of action has remained elusive. The present study investigated whether Rhodiola rosea was able to downregulate the expression of tumor necrosis factor-α-inducible protein 8-like 2 (TIPE2), thereby inhibiting the expression of apoptotic genes, attenuating T-lymphocyte apoptosis and improving immunity in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…Rhodiola rosea extracts increased total CD3+ and memory CD4+ T cell pools, but decreased the number and function of cytotoxic CD8+ T cells in a mouse model of caecal ligation and puncture-induced sepsis [131]. Rhodiola rosea extracts increased production of Th1 cytokines (i.e.…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodiola rosea extracts increased total CD3+ and memory CD4+ T cell pools, but decreased the number and function of cytotoxic CD8+ T cells in a mouse model of caecal ligation and puncture-induced sepsis [131]. Rhodiola rosea extracts increased production of Th1 cytokines (i.e.…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…Rhodiola rosea extracts increased production of Th1 cytokines (i.e. IFN-γ, IL-2 and IL-12), reduced spleen and thymus lymphocyte apoptosis and enhanced their survival through downregulation of tumor necrosis factor-α-induced protein 8-like-2 expression in septic rats [131]. Salidroside not only improved total T cell (CD3+) and Th1 cells (CD4+), but also promoted the production of immunoglobulins (total IgG, IgG1 and IgG2α) for the delayed-type hypersensitivity response to vaccine in aged, 21 months old rats [126].…”
Section: Mechanisms Of Rhodiola Rosea L and Its Active Componentsmentioning
confidence: 99%
“…A study by Liu et al (2015) showed that Rhodiola rosea alcoholic extract markedly decreased the apoptotic rate of thymus lymphocytes in 9 week old BALB/c mice. The authors used Rhodiola rosea extract to treat BALB/c mice with induced sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity increases in recent years, and the age of onset is continuously becoming young. Morbidity of cervical cancer is only next to breast cancer among malignant tumor in women and becomes an important disease that threatens life safety of women [6,7]. Surgery is the main clinical treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%